THE NATURE OF RISK IN ISLAMIC FINANCIAL INSTITUTIONS - Sari, Putri Reno Kemala (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2017)
Islamic financial institutions are a risky business and several risk factors have been identified as critical to ensure that the Islamic financial institutions position remain intact amid the intense competition in the industry. The survival and success of a financial organization depends critically on the efficiency of managing risks. More importantly, good risk management is highly relevant in providing better return to the stakeholders. In addition, prudent risk management by financial institutions is the hallmark to avoid financial distress that could lead to financial crisis. This research aims to identify the types of risk in Islamic Financial Institutions. This research is using qualitative method to collect and analyze the data through direct observation and documentation study. The findings in this study offers a new interpretation of the primary sources that significantly introduce substantial new evidence and findings that would be beneficial for players in the Islamic industry, including policymakers and regulators to develop, enhance and improve the Risk Management. Furthermore, the study hopes to contribute in terms of recommendation strategy to strengthen and knowing the risk of the Islamic Financial Institutions so as to increase the overall competitiveness in the Islamic Financial Industry.